First records of Leucania rawlinsi Adams and L. senescens Möschler (Lepidoptera: Noctuidae) in Brazil: redescription, potential association with Bt maize, larval parasitoids, and spatial and temporal distribution - Cocco, Jéssica; Dolibaina, Diego Rodrigo; Casagrande, Mirna Martins; Specht, Alexandre; Foerster, Luís Amilton (Zootaxa, 2019)
Every year the area of transgenic maize planting in Brazil expands, however, our knowledge of the fauna of herbivorous insects associated with this genetically modified crop is restricted. In this work we report for the first time the occurrence of Leucania rawlinsi Adams, 2001 and L. senescens (Möschler, 1890) (Lepidoptera: Noctuidae) in Brazil with larvae feeding on Bt and non-Bt maize silk, as well as their braconid and tachinid larval parasitoids. In order to facilitate the specific identification of these species in future studies, redescriptions of adults including high resolution images are provided. In addition, spatiotemporal distribution data of both species are presented based on systematic surveys at 13 localities in Brazil and the examination of material deposited in several scientific collections. The results are presented and discussed to contribute to the evaluation of the complex of species associated with agricultural systems that include grass crops, especially maize, including Bt varieties.